EMISSIONS DURING VOLATILES AND CHAR COMBUSTION PERIODS OF DEMINERALIZED LIGNITE AND WOOD BLENDS - Yilgin, Melek; Pehlivan, Dursun (Taylor & Francis Inc, 2011)
Today, much interest has been given to the utilization of materials of plant origin as substitutions of fossil fuels in meeting energy needs to reduce the level of atmospheric pollutant emissions and global warming threat. Special emphasis has been placed on the co-combustion of coal and biomass. In this study, SO2 and NOx emission levels during volatiles evolution and combustion periods of single pellets of one high sulfur content lignite, demineralized lignite, poplar wood, and their blends were studied by burning them in a cylindrical wire mesh basket placed into a preheated tube furnace. Flue gas composition revealed that majority of sulfur-containing components evolved and oxidized to SO2 during volatiles combustion, and no SO2 was involved during the most length of char combustion period. NOx emissions were only in the form of NO, confined mostly in volatile matter combustion periods, and continued after disappearance of volatiles flames in very smaller levels. NO formation can be explained mostly by fuel and volatiles flame NO mechanisms. Except lignite-wood blend, no synergy was observed in the combustion of demineralized lignite-wood blends in terms of pollutant components.
Keywords: Co-combustion; Lignite; Poplar wood; SO2; NOx